2021
DOI: 10.25042/epi-ije.022021.03
|View full text |Cite
|
Sign up to set email alerts
|

A Low Cost Vehicle Counting System Based On The Internet of Things

Abstract: In urban areas where land for parking is very limited, drivers often waste time, fuel, and emissions circling around without information if unoccupied parking spaces are available or not. In this paper, we design and implement a low-cost wireless system to count the number of cars and motorcycles in a parking lot. The system consists of two sensor devices, which are installed at an entrance gate and an exit gate of a parking lot. Each device has a NodeMCU ESP8266, an HC-SR04 ultrasonic sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Applications of the Internet of Things and data mining techniques have been implemented [9], [10] to detect incoming and outgoing vehicles and count how many vehicles are entering and leaving a parking space. In this application, moving objects are classified as cars, motorcycles, or people.…”
Section: Methodsmentioning
confidence: 99%
“…Applications of the Internet of Things and data mining techniques have been implemented [9], [10] to detect incoming and outgoing vehicles and count how many vehicles are entering and leaving a parking space. In this application, moving objects are classified as cars, motorcycles, or people.…”
Section: Methodsmentioning
confidence: 99%
“…[101] This approach scans the environment to find vehicles. [50] Not found publication articles on using this sensor as a solution to this problem at this moment.…”
Section: Ultrasonic Sensormentioning
confidence: 99%
“…It measures the time difference between transmitted and received sound waves to calculate the distance of the obstacle. Ultrasonic sensors are widely used for measuring vehicle flow or free parking slot management [50,51]. The main disadvantage of ultrasonic sensors are their high sensitivity to environmental noises [52].…”
Section: Ultrasonic Sensormentioning
confidence: 99%
“…Priohutomo et al [12] discussed the design of maneuver controls using a microcontroller to avoid the ship from the collision. Sitanayah et al [13] designed and implemented a low-cost wireless system to count the number of cars and motorcycles in a parking lot using the microcontroller. In addition, Putra et al [14] showed the design and development of a simulator that can represent the earthquakes using a microcontroller, the hydraulic actuator and the three-axis accelerometer.…”
Section: Introductionmentioning
confidence: 99%